Hubungan Kompleksitas Regimen Dengan Kepatuhan Minum Obat pada Pasien Gagal Ginjal Kronik di Ruang Hemodialisa RSUD Tidar Kota Magelang - Fatmasari, Luthfi Bintang; Hartoyo, Mugi; Cuciati, Cuciati; Hartono, Rhodi; Budiyati, Budiyati (Universitas Muhammadiyah Magelang, 2024)
Drug regimens for CKD with comorbidities and complications require long-term treatment so that it can interfere with lifestyle and can affect treatment adherence. The purpose of this study was to determine the relationship between regimen complexity and medication adherence in patients with chronic kidney failure in the hemodialysis room of Tidar Hospital, Magelang City. This study used a cross-sectional approach with a population of all patients who routinely undergo hemodialysis in the Hemodialysis Room of Tidar Hospital, Magelang City. The sampling technique used purposive sampling so that a sample of 60 respondents was obtained. Collecting data in this study using a questionnaire. Data analysis using the Kendall Tau correlation test b. The results showed that the majority were male, aged <45 years, the education level was mostly high school, with the most comorbid hypertension, the majority of respondents underwent hemodialysis for more than 24 months, the complexity of the regimen was mild, and the level of adherence to taking medication very obedient. The results of the Kendall Tau b test analysis found that the p value was 0.000, r = +0. 0. 673, so there was a strong relationship between regimen complexity and medication adherence in chronic kidney failure patients at Tidar Hospital, Magelang City. Based on this study, it is expected that patients with chronic kidney failure will continue to improve adherence to taking medication and undergo regular and disciplined hemodialysis therapy for the rest of their lives in order to achieve treatment success and minimize complications in patients with chronic kidney failure.